Powder metallurgy near-net forming method for high-purity iron TD4 thin-wall complex component

By combining low-temperature plasma activation treatment and a functional gradient pressure punch with an electric field-activated pressure-assisted sintering system, sintering parameters are monitored in real time and dynamically adjusted. This solves the problems of insufficient density and cracking in thin-walled complex components made of high-purity iron TD4, achieving high-precision and high-density forming results.

CN121467702AActive Publication Date: 2026-02-06SICHUAN MINSHENG SPECIAL STEEL FORGING CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202610019002.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-08
Publication Date
2026-02-06
Estimated Expiration
2046-01-08

AI Technical Summary

Technical Problem

In traditional powder metallurgy processes, the oxide layer and adsorbed impurities on the surface of high-purity iron powder reduce the bonding strength of the sintering neck, resulting in insufficient density. The mold design is inaccurate, sintering lacks real-time control, and the components have a high cracking rate after cooling, making it difficult to meet the precision and density requirements of high-end equipment.

Method used

TD4 iron powder is activated by low-temperature plasma under argon protection. Combined with a functional gradient pressure punch and an electric field activated pressure assisted sintering system, the deformation of the thin-walled region is monitored in real time and the sintering parameters are dynamically adjusted. After forced cooling, surface treatment is performed to ensure the density and precision of the components.

Benefits of technology

It significantly improves the density and precision of thin-walled complex components made of high-purity iron TD4, reduces the risk of stress cracking after cooling, and meets the precision and density requirements of high-end equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121467702A_ABST
    Figure CN121467702A_ABST
Patent Text Reader

Abstract

The invention discloses a powder metallurgy near-net forming method for a high-purity iron TD4 thin-wall complex component, which belongs to the field of powder metallurgy and comprises the following steps of: 1, activating spherical TD4 iron powder with the Fe content of more than or equal to 99.8 percent and the particle size of 15-45 microns by using low-temperature plasma with the power of 100-300W for 5-15 minutes under the protection of argon; 2, the isostatic pressing graphite die is filled in a vibration mode, a cavity is compensated through the shrinkage rate of 1.2%-2.5%, and a functional gradient punch with a slightly-convex curved surface is arranged; 3, electric field activation pressure auxiliary sintering is conducted, real-time monitoring is conducted through a high-speed camera larger than or equal to 100 fps and a pyrometer, and AI dynamically regulates and controls current and pressure according to curvature variation and the like; and 4, high-purity argon is forcibly cooled at the speed of 50-100 DEG C / min under the pressure maintaining condition, sand blasting and chemical polishing are conducted after demolding, the density and size precision of the component are improved through the method, the thin wall cracking risk is reduced, and the requirement of the high-end field is met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of powder metallurgy, and more particularly to a powder metallurgy near-net forming method for high-purity iron TD4 thin-wall complex component. BACKGROUND

[0002] In the high-end fields of aerospace precision sensing and semiconductor packaging bases, high-purity iron TD4 components become the preferred materials for core key parts due to the excellent magnetic permeability and mechanical stability brought by the iron content of more than 99.8%. In particular, thin-wall complex structure design can achieve lightweight and integration requirements, but the forming precision of such components directly determines the operation precision of terminal equipment, and puts forward strict challenges to manufacturing technology. Powder metallurgy near-net forming becomes the mainstream preparation path for such components due to high material utilization and strong shape replication, but the low activity of high-purity iron powder and the forming vulnerability of thin-wall areas make it difficult for traditional processes to break through the performance bottleneck.

[0003] In the traditional powder metallurgy process, the surface oxide layer and adsorbed impurities of high-purity iron powder can reduce the sintering neck binding strength, resulting in a component density of less than 10%. The mold design mainly uses unified shrinkage compensation, ignoring the sintering shrinkage difference between thin-wall and thick-wall areas, so that the size tolerance is often more than ±0.5 mm. The sintering process relies on empirical parameter setting and lacks real-time monitoring of micro-deformation such as bulging and depression in the thin-wall area. Only relying on post-grinding can easily cause uneven wall thickness. The natural cooling in the cooling stage forms 15-20 MPa residual stress in the component, and the cracking rate in the thin-wall area is more than 12%. The surface treatment is only single sandblasting treatment, which cannot meet the requirements of roughness Ra≤0.8 μm and surface purity, restricting the application of the component in the precision field. With the improvement of component precision requirements of high-end equipment to ±0.1 mm and density ≥98%, the traditional process cannot meet the requirements. The integration of low-temperature plasma activation and AI dynamic control sintering is aimed at the core pain points of high-purity iron thin-wall forming, providing an innovative path to break through the existing technical bottleneck.

[0004] Therefore, the existing technology has the problems of low powder activity, insufficient density, inaccurate mold compensation, no real-time control of sintering, and stress cracking after cooling. SUMMARY

[0005] In order to overcome the problems of low powder activity, insufficient density, inaccurate mold compensation, no real-time control of sintering, and stress cracking after cooling in the existing technology, the present application discloses a powder metallurgy near-net forming method for high-purity iron TD4 thin-wall complex component, which can effectively solve the above technical problems.

[0006] To solve the above technical problems, the technical scheme of the present application is as follows:

[0007] A powder metallurgy near-net forming method for high-purity iron TD4 thin-wall complex component, comprising the following steps:

[0008] The spherical TD4 iron powder prepared by atomization of ultra-high purity gas is subjected to low-temperature plasma activation treatment under argon protection, the Fe content of the TD4 iron powder is ≥99.8%, the total content of impurity elements is ≤0.2%, and the particle size distribution is 15μm-45μm;

[0009] The activated TD4 iron powder after the activation treatment is filled into the cavity of a high-precision graphite mold under vibration, the cavity of the graphite mold is designed with shrinkage compensation, and is provided with a functionally graded pressure punch, and the functionally graded pressure punch is provided with a micro-convex curved surface structure corresponding to the thin-walled region of the component;

[0010] The mold and the powder are sintered by using an electric field activated pressure assisted sintering system, the system includes a FAST device, a double-wavelength pyrometer, a high-speed industrial camera with a built-in micro high-temperature optical probe, and an AI processing unit, the high-speed camera collects real-time images of the thin-walled region of the component, the pyrometer monitors the real-time temperature, and the AI processing unit dynamically adjusts the pulse current density, the pressing pressure, and the punch down speed according to the comparison result of the image calculated deformation quantitative index and the preset threshold value;

[0011] After sintering, high-purity argon is introduced to cool to room temperature under the condition of maintaining pressure, and the high-purity iron TD4 thin-walled complex component is obtained after surface treatment after demolding.

[0012] Preferably, the parameters of the low-temperature plasma activation treatment are: plasma power 100W-300W, treatment time 5min-15min, and argon flow rate 20L / h-50L / h.

[0013] Preferably, the graphite mold is made of isostatic pressing graphite, the shrinkage compensation amount of the cavity is 1.2%-2.5%, and the surface roughness Ra of the cavity corresponding to different wall thickness regions of the component is ≤0.8μm.

[0014] Preferably, the convex height of the micro-convex curved surface structure of the functionally graded pressure punch is 0.05mm-0.2mm, the curvature radius is 5mm-20mm, and the hardness of the convex region is 10%-15% higher than that of the punch body.

[0015] Preferably, the initial parameters of the electric field activated pressure assisted sintering are set as: the highest sintering temperature is 950℃-1050℃, the initial pressure is 20MPa-50MPa, the heating rate is 100℃ / min-300℃ / min, and the pulse current frequency is 50Hz-200Hz.

[0016] Preferably, the acquisition frame rate of the high-speed industrial camera is ≥100fps, and the image resolution is ≥2048×1536 pixels, the camera shoots through a quartz observation window reserved on the side wall of the mold, and the light transmittance of the observation window is ≥90%.

[0017] Preferably, the deformation quantization index comprises the real-time curvature change amount and deformation rate of the thin-walled area, and in the preset threshold, the curvature change amount threshold is 0.01mm -1 -0.03mm -1 , and the deformation rate threshold is 0.001mm / s-0.005mm / s.

[0018] Preferably, the specific way of dynamic regulation is: when the deformation rate exceeds the threshold and shows a concave trend, the pulse current density of the corresponding area is reduced by 5%-15%, and the pressing pressure is increased by 3%-8%; when the deformation rate exceeds the threshold and shows a bulging trend, the pulse current density of the corresponding area is increased by 5%-15%, and the punch down speed is reduced by 10%-20%.

[0019] Preferably, the forced cooling argon has a purity of ≥99.999%, a cooling rate of 50℃ / min-100℃ / min, and the pressurization is stopped when the cooling temperature is below 200℃.

[0020] Preferably, the surface treatment comprises sandblasting treatment and chemical polishing, the sandblasting uses alumina abrasive with a particle size of 50μm-100μm, and the pressure is 0.1MPa-0.3MPa; the chemical polishing uses a mixed solution of nitric acid and hydrofluoric acid with a volume ratio of 3:1, and the treatment time is 30s-60s.

[0021] Compared with the prior art, the beneficial effects of the present application are: the present application aims at the problem of low activity and insufficient density of powder, adopts low-temperature plasma activation treatment under argon protection, and 100W-300W power plasma can effectively remove the surface oxide layer and adsorbed impurities of TD4 iron powder, and 5min-15min processing time length is matched with 20L / h-50L / h argon flow, which can avoid powder pollution while improving surface activity, make the sintering neck between powder particles combine more closely, and greatly improve the density of the component; for the problem of inaccurate mold compensation, an isostatic pressing graphite mold is used to compensate the cavity by 1.2%-2.5%, and a functionally graded punch with a 0.05mm-0.2mm raised height micro-convex surface is arranged in the corresponding thin-walled area, which can accurately match the sintering shrinkage difference and stress demand of different wall thickness areas, solve the size deviation problem, and the roughness of the cavity Ra≤0.8μm can guarantee the forming precision; for the problem of no real-time regulation of sintering, a high-speed camera with a speed of ≥100fps and a dual-wavelength pyrometer are used in the electric field activation pressure-assisted sintering system to collect images and temperature of the thin-walled area in real time, and an AI processing unit dynamically regulates according to the curvature change and other indicators, reduces the current by 5%-15% and increases the pressure by 3%-8% when the punch is concave, and increases the current by 5%-15% and reduces the punch speed by 10%-20% when the punch is convex, which can prevent sintering deformation; for the problem of cold stress cracking, 99.999% high-purity argon is introduced in the pressure maintaining state after sintering, and forced cooling is carried out at a rate of 50℃ / min-100℃ / min, the design of stopping pressure below 200℃ can inhibit abnormal grain growth and reduce internal stress accumulation, and then the combination of sand blasting and chemical polishing can not only guarantee the surface quality but also further eliminate the surface stress, and comprehensively improve the comprehensive performance of the component. BRIEF DESCRIPTION OF DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings needed to be used in the following embodiment or prior art description will be briefly introduced. Obviously, the drawings in the following description are only exemplary, and other drawings can be obtained by the provided drawings without creative labor for those skilled in the art.

[0023] Fig. 1 Process structure diagram of the present application;

[0024] Fig. 2 Process method step diagram of the present application. DETAILED DESCRIPTION

[0025] The drawings are only used for illustrative description and cannot be understood as a limitation of the present patent;

[0026] In order to better illustrate the present embodiment, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product;

[0027] It will be appreciated by those skilled in the art that certain known structures and their descriptions may be omitted from the drawings for the sake of clarity.

[0028] The technical solutions of the present application will be further described below in combination with the drawings and examples.

[0029] Examples

[0030] Please refer to Figs. 1-2 A powder metallurgy near-net forming method for high-purity iron TD4 thin-walled complex component, comprising the following steps:

[0031] The spherical TD4 iron powder prepared by super-high-purity gas atomization is subjected to low-temperature plasma activation treatment under argon protection, the Fe content of the TD4 iron powder is greater than or equal to 99.8%, the total content of impurity elements is less than or equal to 0.2%, and the particle size distribution is 15-45 microns;

[0032] The activated TD4 iron powder after activation treatment is filled into the cavity of a high-precision graphite mold under vibration, the cavity of the graphite mold is designed with shrinkage compensation, and is provided with a functional gradient pressure punch, and the functional gradient pressure punch is provided with a micro-convex curved surface structure corresponding to the thin-walled region of the component;

[0033] A field-activated pressure-assisted sintering system is used for sintering the mold and the powder, the system comprises a FAST device, a dual-wavelength pyrometer, a high-speed industrial camera with a built-in micro high-temperature optical probe, and an AI processing unit, real-time images of the thin-walled region of the component are collected by the high-speed camera, the real-time temperature is monitored by the pyrometer, and the pulse current density, the pressing pressure, and the punch down speed are dynamically controlled according to the comparison result of the image calculated deformation quantitative index and the preset threshold value by the AI processing unit.

[0034] After sintering is completed, high-purity argon is introduced to forcibly cool to room temperature under the condition of maintaining pressure, and a high-purity iron TD4 thin-walled complex component is obtained after surface treatment after demolding.

[0035] The parameters of the low-temperature plasma activation treatment are as follows: plasma power 100-300 W, treatment time 5-15 min, and argon flow rate 20-50 L / h.

[0036] The graphite mold is made of isostatic pressing graphite, the shrinkage compensation amount of the cavity is 1.2%-2.5%, and the surface roughness Ra of the cavity corresponding to different wall thickness regions of the component is less than or equal to 0.8 microns.

[0037] The convex height of the micro-convex curved surface structure of the functional gradient pressure punch is 0.05-0.2 mm, the curvature radius is 5-20 mm, and the hardness of the convex region is 10%-15% higher than that of the punch body.

[0038] The initial parameters of the electric field activated pressure assisted sintering are as follows: the maximum sintering temperature is 950-1050 DEG C, the initial pressure is 20-50 MPa, the heating rate is 100-300 DEG C / min, and the pulse current frequency is 50-200 Hz.

[0039] The acquisition frame rate of the high-speed industrial camera is greater than or equal to 100 fps, and the image resolution is greater than or equal to 2048*1536 pixels, and the quartz observation window reserved on the side wall of the mold is used for shooting, and the light transmittance of the observation window is greater than or equal to 90%.

[0040] The deformation quantization index includes the real-time curvature change amount and the deformation rate of the thin-walled area, and in the preset threshold, the curvature change amount threshold is 0.01 mm -1 -0.03 mm -1 , and the deformation rate threshold is 0.001-0.005 mm / s.

[0041] The specific mode of dynamic regulation is: when the deformation rate exceeds the threshold and shows a concave trend, the pulse current density of the corresponding area is reduced by 5-15%, and the pressing pressure is increased by 3-8%; when the deformation rate exceeds the threshold and shows a bulging trend, the pulse current density of the corresponding area is increased by 5-15%, and the punch down speed is reduced by 10-20%.

[0042] The forced cooling argon has a purity of greater than or equal to 99.999%, a cooling rate of 50-100 DEG C / min, and stops pressing when cooled to below 200 DEG C.

[0043] The surface treatment includes sand blasting and chemical polishing, the sand blasting uses alumina abrasive with a particle size of 50-100 um, and the pressure is 0.1-0.3 MPa; the chemical polishing uses a mixed solution of nitric acid and hydrofluoric acid with a volume ratio of 3:1, and the treatment time is 30-60 s.

[0044] This embodiment takes the preparation of a U-shaped high-purity iron TD4 thin-walled complex component for a high-end electronic device as the object, the component has an opening width of 60 mm, a depth of 40 mm, a main body wall thickness of 1.0 mm, three waist-shaped holes with a diameter of 4 mm distributed on each side wall, and an arc-shaped transition section with a curvature radius of 10 mm at the bottom, and the technical requirements are as follows: the density is greater than or equal to 98.5%, the size tolerance is less than or equal to ±0.1 mm, the surface roughness Ra is less than or equal to 0.6 um, there is no internal crack and surface defect, and the following is the complete implementation process that meets the technical scheme requirements, and the key parameters strictly follow the scheme limited range.

[0045] The spherical TD4 iron powder prepared by the super-high purity gas atomization process is selected, and the core indicators are detected according to the standard process: the Fe content is 99.8%, the total content of impurity elements is 0.2% (among which the proportions of C, Si, Mn and other conventional impurities are each ≤0.05%), the particle size distribution is 15-45 μm, and the laser particle size instrument test shows that the D50 is 30 μm, which meets the basic requirements of the technical scheme for the raw material.

[0046] To remove the trace amount of water and oil stains adsorbed on the surface of the iron powder, the screened iron powder is placed in a vacuum drying box, the temperature is set to 80°C, the vacuum degree is-0.09 MPa, and the drying time is 4 h. After drying, it is immediately transferred to a sealed container under argon protection to avoid oxidation caused by contact with air.

[0047] The activation operation is performed by using a radio frequency low temperature plasma treatment equipment, and the core parameters are strictly set according to the optimization range of the technical scheme. First, the dried TD4 iron powder is evenly laid in a quartz reaction boat, and the laying thickness is controlled to be 5 mm to ensure that the plasma can uniformly act on the surface of the powder. The reaction boat is sent into the reaction chamber, and after the chamber is closed, it is vacuumed to 1×10 -3 Pa, then high-purity argon is introduced, the flow rate is adjusted to 30 L / h, and after the chamber pressure is stabilized at 0.05 MPa, the plasma generating device is started.

[0048] The plasma power is set to 200 W, and the treatment time is 10 min. During the activation process, the oxygen content monitor built-in the chamber is used for real-time monitoring to ensure that the oxygen content in the chamber is ≤0.01% to avoid secondary oxidation of the iron powder. After the treatment is completed, the argon gas is kept flowing until the chamber is naturally cooled to room temperature. The activated iron powder is taken out and transferred into a sealed container for standby. After detection, the thickness of the oxidation layer on the surface of the activated iron powder is reduced by 60% compared with before treatment, and the powder flowability is improved by 30%, which lays a foundation for uniform filling and high-density forming.

[0049] The isostatic pressing graphite is used as the mold base material, which has excellent high temperature resistance and dimensional stability, meeting the requirements of the technical scheme. According to the sintering shrinkage characteristics of the component, the simulation calculation shows that the cavity shrinkage compensation amount is 1.8% (in the optimization range of 1.2%-2.5%), and accordingly the mold cavity size is designed as follows: opening width 61.08 mm, depth 40.72 mm, main body wall thickness 1.018 mm, and the waist hole size is enlarged by 1.8% in proportion.

[0050] The mold processing adopts a five-axis numerical control milling machine. After rough machining, a 0.2 mm finishing allowance is reserved. Diamond cutters are selected for finishing, with a cutting speed of 80 m / min and a feed rate of 0.05 mm / r. For the thin-walled and waist-shaped hole structures of the component, the cavity surface is polished by diamond grinding wheel. The surface roughness Ra of each area is ≤0.8 μm, meeting the requirements of the scheme. A 10 mm diameter mounting hole is machined on the side wall of the mold corresponding to the arc transition section of the component. A quartz observation window with a light transmittance of 90% is embedded for real-time monitoring of the thin-walled area during sintering. The observation window and the mold are sealed with high-temperature sealant to ensure air tightness.

[0051] The punch body is made of high-strength hard alloy material. According to the stress characteristics of the thin-walled area of the component, a micro convex surface structure is machined at the positions corresponding to the main wall thickness and the arc transition section. The micro convex surface parameters strictly follow the scheme optimization range: the convex height of the main thin-walled corresponding area is 0.1 mm, and the curvature radius is 15 mm; the convex height of the arc transition section corresponding area is 0.15 mm, and the curvature radius is 10 mm.

[0052] To achieve the hardness gradient requirement, local quenching is performed on the micro convex surface area. After treatment, the hardness of the convex area is 12% higher than that of the punch body (within the range of 10%-15%), which can apply targeted pressure to the thin-walled area during pressing to avoid local density deficiency or deformation. After the punch is processed, surface polishing is performed to ensure that the gap between the punch and the mold cavity is ≤0.02 mm.

[0053] The processed graphite mold is fixed on the workbench of the vibration filling equipment, and the horizontal degree of the mold is adjusted to an error of ≤0.02 mm / m. The vibration device is started, the vibration frequency is set to 50 Hz, and the amplitude is set to 0.5 mm. The activated TD4 iron powder is slowly poured into the mold inlet, and the vibration is used to make the powder flow fully inside the cavity and fill the complex structure areas such as the waist-shaped hole and the arc transition section.

[0054] During the filling process, the powder accumulation density is monitored in real time by the pressure sensor at the bottom of the mold. When the pressure stabilizes at 0.3 MPa, the vibration is stopped, and the powder accumulation density reaches 2.8 g / cm³. The excess powder is scraped off along the upper surface of the mold to ensure that the powder is flush with the upper edge of the mold. Then, a graphite cover plate is covered to complete the filling operation. The mold is transferred to the workbench of the electric field activation pressure-assisted sintering system.

[0055] The sintering system is configured according to the technical scheme: taking the FAST device as the core, matched with a double-wavelength pyrometer, a high-speed industrial camera with a built-in miniature high-temperature-resistant optical probe and an AI processing unit, the high-speed industrial camera is installed in front of the quartz observation window on the side wall of the mold, the frame rate is set to 100 fps, the image resolution is 2048x1536 pixels, and the real-time image of the thin-walled area is captured clearly; the double-wavelength pyrometer is aligned with the center area of the mold cavity, the measurement range covers 500-1200℃, the accuracy is ±5℃, and it is used for real-time monitoring of the sintering temperature.

[0056] In the debugging stage, the standard curvature sample is put into the mold to simulate the sintering temperature rising process, and the deformation amount calculation accuracy of the AI processing unit is verified: the error between the curvature change amount calculated by the image recognition algorithm and the actual measured value is ≤0.002mm -1 , the deformation rate calculation error is ≤0.0005mm / s, and the accuracy of monitoring and control is ensured.

[0057] According to the preferred parameter range of the technical scheme, the initial sintering parameters are set: the highest sintering temperature is 1000℃, the initial pressure is 35MPa, the temperature rising rate is 200℃ / min, and the pulse current frequency is 100Hz; the deformation amount index threshold is set: the curvature change threshold is 0.02mm -1 , the deformation rate threshold is 0.003mm / s, and the dynamic control rule strictly follows the scheme requirements.

[0058] The assembled mold is sent into the FAST device sintering cavity, and after the chamber is closed, it is vacuumed to 1x10 -3 Pa, then high-purity argon is introduced to 0.1MPa, the sintering program is started, in the temperature rising stage, the double-wavelength pyrometer feeds back the temperature data in real time, the AI processing unit maintains the temperature rising rate stable by adjusting the pulse current density, when the temperature rises to 1000℃, it enters the holding stage, and the holding time is 5min.

[0059] During the holding process, the high-speed industrial camera continuously collects the images of the arc transition section and the thin-walled area around the waist-shaped hole of the component, and the AI processing unit calculates the deformation amount index every frame, when the deformation rate of the arc transition section reaches 0.004mm / s and shows a bulging trend, the AI unit immediately outputs the control instruction: the pulse current density of the corresponding area is increased by 10%, the punch down pressure is reduced by 15%, and after 3s, the deformation rate is reduced to 0.0025mm / s; then the deformation rate of the area around the waist-shaped hole is monitored to be 0.0045mm / s and shows a concave trend, and the control instruction is to reduce the pulse current density by 10% and increase the pressing pressure by 5%, and after 5s, it returns to the threshold, and the whole holding stage executes dynamic control 5 times, ensuring that the deformation amount of each thin-walled area is always within the controllable range.

[0060] After the sintering and heat preservation is completed, a forced cooling process is started, the initial pressure of 35 MPa is kept unchanged, high-purity argon with a purity of 99.999% is introduced, the argon flow is adjusted through a flow control system to stabilize the cooling rate at 80 ℃ / min (in the range of 50 ℃ / min-100 ℃ / min), a dual-wavelength pyrometer is used to monitor the component temperature in real time, when the temperature drops below 200 ℃, the AI unit issues a pressure release instruction, the pressure is reduced to normal pressure at a rate of 0.2 MPa / s, and the argon continues to be introduced until the component is naturally cooled to room temperature.

[0061] During the forced cooling process, the internal stress of the component is monitored through a stress sensor, the peak value is ≤15 MPa, which is much lower than the 30 MPa of the traditional cooling method, effectively avoiding the risk of stress cracking.

[0062] After the cooling is completed, the sintering chamber is opened to take out the mold, a hydraulic demolding device is used for demolding, the demolding pressure is set to 10 MPa, and the demolding speed is 5 mm / s, the component is separated from the mold cavity by slowly applying pressure, avoiding damage to the thin-walled area due to uneven stress, and the initial formed component is obtained after demolding, and there is no obvious depression, bulging or crack in appearance inspection.

[0063] The surface treatment adopts a combined process of sand blasting and chemical polishing according to the technical scheme, first sand blasting treatment is carried out: select alumina abrasive with a particle size of 80 μm, adjust the sand blasting pressure to 0.2 MPa (in the range of 0.1 MPa-0.3 MPa), the sand blasting distance is 300 mm, the treatment time is 20 s, the surface scale and graphite residue of the component are removed, and the surface dust is blown clean after sand blasting, and then the chemical polishing process is entered.

[0064] A mixed solution of nitric acid and hydrofluoric acid with a volume ratio of 3:1 is prepared, the component is completely immersed in the solution, the treatment time is 45 s (in the range of 30 s-60 s), low-speed stirring is used during the treatment to ensure uniform polishing, after the treatment is completed, the component is immediately placed in deionized water for washing until the pH value is 7, and then it is transferred into a vacuum drying box and dried at 80 ℃ for 30 min.

[0065] According to the technical requirements, the finished component is subjected to full inspection: the Archimedes drainage method is used to detect the density of 98.8%, which meets the requirement of ≥98.5%; the size measurement shows that the opening width is 59.95 mm, the depth is 39.92 mm, and the main body wall thickness is 0.99 mm, and the tolerances of each size are all ≤±0.1 mm; the surface roughness instrument detects that the Ra is 0.5 μm, which meets the standard of ≤0.6 μm; the ultrasonic flaw detection shows that there is no internal crack, and the X-ray fluorescence spectrum analysis shows that there is no impurity pollution on the surface; in the mechanical property test, the tensile strength is 420 MPa, and the yield strength is 380 MPa, which meets the use requirements.

[0066] The embodiment successfully prepares the high-purity iron TD4 thin-wall complex component meeting the requirements by performing the parameters and the process in the technical scheme, and verifies the feasibility and stability of the forming method.

[0067] The same or similar reference signs correspond to the same or similar components;

[0068] The terms describing the positional relationship in the drawings are only used for example illustration, and should not be understood as a limitation to the patent;

[0069] Obviously, the above embodiments of the present application are merely exemplary for clearly illustrating the present application, and are not intended to limit the implementation modes of the present application. For those skilled in the art, on the basis of the above description, other different forms of changes or variations can be made, and here, all the implementation modes do not need to be exhausted, and it is impossible to exhaust all the implementation modes. Any modification, equivalent replacement and improvement made within the spirit and principle of the present application should be included in the protection scope of the claims of the present application.

Claims

1. A near-net-shape powder metallurgy forming method for thin-walled complex components made of high-purity iron TD4, characterized in that, Includes the following steps: Spherical TD4 iron powder prepared by ultra-high purity gas atomization was subjected to low-temperature plasma activation treatment under argon protection. The TD4 iron powder had an Fe content ≥99.8%, a total impurity element content ≤0.2%, and a particle size distribution of 15μm-45μm. The activated TD4 iron powder is filled into the cavity of a high-precision graphite mold under vibration. The cavity of the graphite mold is designed with shrinkage compensation and is equipped with a functional gradient pressure punch. The functional gradient pressure punch has a micro-convex curved surface structure in the thin-walled area of ​​the component. An electric field activated pressure-assisted sintering system is used to sinter molds and powders. The system includes a FAST device, a dual-wavelength pyrometer, a high-speed industrial camera with a built-in miniature high-temperature resistant optical probe, and an AI processing unit. The high-speed camera acquires real-time images of the thin-walled area of ​​the component, the pyrometer monitors the real-time temperature, and the AI ​​processing unit dynamically adjusts the pulse current density, pressing pressure, and punch pressing speed based on the comparison results of the deformation index calculated from the image and the preset threshold. After sintering, high-purity argon gas is introduced under pressure to force cooling to room temperature. After demolding, surface treatment is performed to obtain high-purity iron TD4 thin-walled complex components.

2. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The parameters for the low-temperature plasma activation treatment are: plasma power 100W-300W, treatment time 5min-15min, and argon flow rate 20L / h-50L / h.

3. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The graphite mold is made of isostatically pressed graphite, and the shrinkage compensation of the cavity is 1.2%-2.5%. The surface roughness Ra of the cavity in different wall thickness areas of the corresponding component is ≤0.8μm.

4. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The protrusion height of the micro-convex curved surface structure of the functional gradient pressure punch is 0.05mm-0.2mm, the radius of curvature is 5mm-20mm, and the hardness of the protrusion area is 10%-15% higher than that of the punch body.

5. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The initial parameters for the electric field activated pressure-assisted sintering are set as follows: maximum sintering temperature 950℃-1050℃, initial pressure 20MPa-50MPa, heating rate 100℃ / min-300℃ / min, and pulse current frequency 50Hz-200Hz.

6. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The high-speed industrial camera has a frame rate of ≥100fps and an image resolution of ≥2048×1536 pixels. It takes pictures through a quartz observation window reserved on the side wall of the mold, and the light transmittance of the observation window is ≥90%.

7. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The deformation metrics include the real-time curvature change and deformation rate of the thin-walled region. The preset threshold for curvature change is 0.01 mm. -1 -0.03mm -1 The deformation rate threshold is 0.001 mm / s-0.005 mm / s.

8. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The specific method of dynamic control is as follows: when the deformation rate exceeds the threshold and shows a concave trend, the pulse current density in the corresponding area is reduced by 5%-15%, while the pressing pressure is increased by 3%-8%; when the deformation rate exceeds the threshold and shows a bulging trend, the pulse current density in the corresponding area is increased by 5%-15%, while the punch pressing speed is reduced by 10%-20%.

9. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The argon gas used for forced cooling has a purity of ≥99.999%, a cooling rate of 50℃ / min-100℃ / min, and pressurization is stopped when the temperature drops below 200℃.

10. The near-net-shape powder metallurgy forming method for high-purity iron TD4 thin-walled complex components as described in claim 1, characterized in that, The surface treatment includes sandblasting and chemical polishing. Sandblasting uses alumina abrasive with a particle size of 50μm-100μm and a pressure of 0.1MPa-0.3MPa. Chemical polishing uses a mixed solution of nitric acid and hydrofluoric acid with a volume ratio of 3:1 and a treatment time of 30s-60s.

Citation Information

Patent Citations

  • Preparation method of dual-scale titanium alloy material

    CN107475547A

  • Multi-zone heterogeneous material composite structure warm-hot extrusion die and preparing method thereof

    CN108817117A

  • Online monitoring device and method for tensile deformation process of electric shock auxiliary bearing steel

    CN115121687A

  • High-strength hard alloy and preparation method and application thereof

    CN119177387A

  • Pressure control method and system for products produced by high-precision steel frame punching machine and computer equipment

    CN119659079A